Aplicações da trigonometria ao ensino de ondulatória utilizando o geogebra - MAGALHÃES, Ricardo Sérgio Medeiros (2018)
This work proposes a teaching methodology of Trigonometry and Ondulatory, addressing the theory of meaningful learning using Geogebra software and a wave simulator. The basis of the research is the comparison of the periodic physical phenomena and the harmonic trigonometric functions. The proposal is implemented through daily applications of the students of the courses 2016 Electronic and Classrooms 2016 of the Federal Institute of Technology of Santa Ines in Maranhão.